Comparative-Historical Analysis - Valenzuela, J. (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course introduces students to basic techniques of historical methodology and to comparative research designs. Not all comparative research in the social sciences (sociology, political science, economics, or cultural anthropology) need be of a historical nature; many questions about contemporary phenomena can be – an only be – addressed with a comparative approach; And not all social science uses of historical evidence need to employ comparative analysis, although. both often go together. Social scientists whose questions lead them to examine historical evidence are not primarily interested in reconstructing an understanding and a sequence (i.e., a narrative) of particular events – which is what most historians attempt to do – but rather they hope to create or further develop concepts and theories that can answer questions about social, political, economic, or cultural processes. This conceptual and theoretical intent often leads social scientists to search for generalities about the phenomena they study, which entails paying close attention to the similarities and differences in the way the phenomena develop in various settings. Hence, most social scientists using historical materials, at one point or another, must draw their inferences using a comparative approach.